Misunderstood: Educator and Practitioner Perceptions of Respiratory Therapy Professional Identity (Higher Education Politics and Economics, 2026)
No current literature explores how respiratory therapists describe their professional identity. To address this gap, this descriptive phenomenological study used stakeholder theory (Freeman, 1994) as a framework to explore the perspectives of practitioners and educators through the use of semi-structured interviews. Participants were asked to share perspectives about professional identity, minimum degree requirements for entry-into-practice, and the clinical implications for identity and practice. The purpose of this study was to explore how increasing professional education expectations may change the professional identity and clinical practice. This exploratory study found a lack of cohesive identity often ascribed to therapists rather than determined by therapists and problematizes future research about respiratory care identity, teaching, and clinical care. Implications for practice include recommendations for focused reflective practice and increased socialization within the profession.